Studi Hadis tentang Ahl al-Bait dalam Perspektif Sunni dan Syiah: A Study of Hadith on Ahl al-Bait from Sunni and Shia Perspectives - Al Furqon Al Furqon (Fenomena, 2012)
The discussion about Sunni and Shia seems never-ending. These two major schools of thought in Islam have different concepts in many aspects. One of the main issues in their historical journeys is the problem of the existence of the Ahl al-Bait of the Prophet Muhammad (PBUH). Both schools agree that the Ahl al-Bait of the Prophet holds a special position in the hearts of Muslims based on authentic hadiths. However, regarding who constitutes the Ahl al-Bait of the Prophet, the two schools differ in their opinions. This research aims to explore more comprehensive information about who the Ahl al-Bait of the Prophet is, based on hadiths from Sunni and Shia traditions. Diskusi tentang Sunni dan Syiah seolah tidak pernah berakhir. Kedua mazhab besar dalam Islam memiliki konsep yang berbeda dalam banyak hal. Salah satu isu utama dalam perjalanan sejarah keduanya adalah masalah eksistensi Ahl al-Bait Rasulullah saw. Kedua mazhab sepakat bahwa Ahl al-Bait Rasulullah saw memiliki posisi khusus di hati umat Islam berdasarkan hadis-hadis yang sahih. Namun, mengenai siapa yang dimaksud dengan Ahl al-Bait Rasulullah saw, kedua mazhab memiliki pendapat yang berbeda dalam menentukannya. Penelitian ini bertujuan untuk menggali informasi lebih komprehensif tentang siapa Ahl al-Bait Rasulullah saw berdasarkan hadis-hadis dari kalangan Sunni dan Syiah.